The population dynamics of Carcinus maenas (Crustacea: Portunoidea) in a coastal lagoon (Portugal, SW) - Teresa Portela; Dénnis Cruz; Rui Monteiro; Maria João Correia; José Lino Costa; Isabel Domingos (Scientia Marina, 2023)
The green crab (Carcinus maenas) population was investigated in a coastal lagoon (Santo André) located on the southwest coast of Portugal. This study assessed the spatial-temporal variability of green crab abundance in the lagoon and its relationship with environmental variables. Experimental fishing was used to collect data on abundance, size structure and other demographic characteristics. Sampling was conducted monthly in 2019 at five sites, using fyke nets. From a total of 15063 individuals collected, 3898 were analysed. The highest catches were obtained in winter and at sites closer to the sea. The population was male-biased (58.70% of males and 41.30% of females), with an average carapace width of 48.81 mm for males and 40.79 mm for females. Ovigerous females were most abundant in December and January, and 50% were sexually mature at 45.11 mm. Based on data from the experimental fishing and fishermen’s logbooks, the estimated annual catch of green crab ranged from 1873 to 3354 kg/ha, confirming the potential value of its fishery in the lagoon. This resource can be exploited for multiple purposes, including its meat or shell waste, thus contributing to the circular economy. Considering that green crab is a bycatch of the eel fishery, fishing regulations need to be modified to safeguard the stocks of both species.